56th Electronic Components and Technology Conference 2006
DOI: 10.1109/ectc.2006.1645747
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Optical Interconnect on Organic Circuit Board

Abstract: We propose high speed optical interconnection which is three dimensional optical lanes using polymer materials fabricated on an organic circuit board with metal lines and pads. These optical lanes transmit optical signals not only on a plane surface but into the other side of a circuit board. It has following three particular portions; (1) Curved parallel optical waveguide; (2) 45 degree reflection mirror; (3) Optical via hole.Four channel three dimensional optical lanes with current electrical lines and pads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Some studies have been reported to form optical through holes in electric circuit boards [8,9]. However, to simplify the fabrication process and to reduce optical loss, the elimination of optical through holes has been desired.…”
Section: Structure Of the Foecbmentioning
confidence: 99%
“…Some studies have been reported to form optical through holes in electric circuit boards [8,9]. However, to simplify the fabrication process and to reduce optical loss, the elimination of optical through holes has been desired.…”
Section: Structure Of the Foecbmentioning
confidence: 99%
“…[6][7][8] In particular, multi-mode polymer optical waveguides are very useful for short transmission lengths, for example with in-shelf connection such as that needed for inter-and intra-board connection in servers and routers. 9,10) Multi-mode waveguides have a large core size of about 50 m square, which facilitates the alignment of the waveguide and the fiber cores. 11) This is effective in reducing the assembly cost.…”
Section: Introductionmentioning
confidence: 99%
“…The first demonstration is the feasibility of on-board, chip-to-chip optical interconnections using three dimensional optical lines consists of multi-channel, S-shape multimode polymer optical waveguides, mirrors, optical via holes for vertical transmission lines. Optical transmitter and receiver circuits were assembled onto the substrate with flip-attached VCSEL and PIN-Photodetector (PIN-PD) [9] .…”
Section: Introductionmentioning
confidence: 99%